Assessment of Item Parameter and Model-Data Fit of 4IR Teachers' Effectiveness Scale in Secondary Schools - Adamu, Chidubem Deborah (Research in Social Sciences and Technology, 2024)
In secondary schools in Southwest Nigeria, the Fourth Industrial Revolution Chemistry Teachers Effectiveness Scale (4IRCTES) items were evaluated for discrimination item parameter and model-data fit to the underlying construct. In this study, a descriptive survey research design was employed. The survey encompassed 4,986 Chemistry teachers in the southwestern region of Nigeria. 35 Chemistry teachers made up the study’s sample. 4IRCTES was the instrument utilised to collect the data. Research question two was based on the absolute overall model-data fit, or M2 statistic, whereas research question one used the Multidimensional Graded Response Model (MGRM) of the Item Response Theory (IRT) to analyse the item parameter (item discrimination). Result showed that items of 4IRCTES discriminated well between teachers with low effectiveness and teachers with high effectiveness. Finally, in the study, result showed that the MGRM of the IRT is the substantial model-data fit for the 4IRCTES. The study concluded that the 4IRCTES items effectively distinguished between teachers who were ineffective and those who were effective.